DOP78 The differential diagnosis and clinicopathological spectrum of Inflammatory Bowel Disease: An interesting and informative ECCO topical review. (27th May 2021) - Feakins, R M; Torres, J; Borralho-Nunes, P; Burisch, J; Cúrdia Gonçalves, T; De Ridder, L; Driessen, A; Lobatón, T; Menchén, L; Mookhoek, A; Noor, N; Svrcek, M; et al.
Abstract: Background: A wide variety of intestinal and non-intestinal diseases can resemble chronic idiopathic inflammatory bowel disease (IBD) clinically and/or pathologically. The aim of the current Topical Review was to explore the differential diagnosis of IBD and to discuss clinical, histomorphological features and ancillary techniques that help distinguish between IBD and its mimics. Methods: An open ECCO call led to the selection of 12 participants who formed three working groups (WG) to study the mimics of IBD. WG 1 comprised gastroenterologists, who explored mainly the clinical features. WG 2 consisted of histopathologists, who focused on macroscopic and microscopic pathological aspects. WG 3 was a mixed group of pathologists and clinicians who studied the value of additional investigative techniques such as imaging, serology and molecular markers. A systematic literature search allowed exploration of these topics and the identification of the most helpful and relevant distinguishing features. The process led to the development of Current Practice Position (CPP) statements and supporting text. Consensus meetings with voting by all participants facilitated modification and finalisation of CPP statements. Results: The project highlighted several points. Firstly, there is a wide and sometimes overwhelming variety of potential mimics of new and established IBD, both in adults and in children. Secondly, some mimics are more important clinically and others pathologically, meaning that the emphasis on the mimics of IBD is different for clinicians and pathologists. Thirdly, close attention to all clinical features, pathological findings and other evidence optimises accuracy. Finally, newer techniques sometimes have a role, e.g., in distinguishing monogenic IBD-like disorders from IBD in young children, and the value of many novel techniques is as yet uncertain. A practical message is that constant awareness by clinicians and pathologists of the possibility of mimics is particularly important. Conclusion: Discussions between pathologists and clinicians were particularly useful during this process and were a reminder of the importance of clinicopathological correlation. There is a wide variety of mimics of IBD, including infections, diverticular disease, drug effect, radiation damage, immune disorders, vascular disorders and diversion proctocolitis. An important, relatively new, and sometimes very close mimic of IBD is immune checkpoint inhibitor colitis. In turn, reliable distinction between IBD and other entities requires a multidisciplinary approach with a full clinical history (including duration of disease), and with appropriate investigations that may include endoscopy, pathology, imaging, microbiological tests, serology, and newer molecular tests.